Mapping the past plotting the future. GIS in archaeology, maturity and implementation, Proceedings of the workshop organised by the AeGIS Athena Lab, at the British School at Athens, Thursday 30 March 2023 - Evangelidis , Vassilis; Tsiafaki , Despoina; Mourthos , Yiannis; Karta , Melpomeni (Journal of Greek Archaeology, 2024)
Conference proceedings comprise nine of the thirteen papers that were initially presented at the international workshop entitled ‘Mapping the Past, Plotting the Future. GIS in archaeology, maturity and implementation’, organized by the AeGIS Athena Lab along with one additional contribution from one of the moderators who actively participated in the concluding discussion. The workshop took place on March 30, 2023, at the British School at Athens.